2012
DOI: 10.1097/mlr.0b013e3181d56926
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Predialysis Therapeutic Practices on Patient Outcomes During the First Year of Dialysis

Abstract: This study suggests that quality of predialysis therapeutic practices is positively associated with survival during the first year of dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…In a cohort study of 556 patients initiating dialysis, receipt of quality care in the management of CKD-related complications prior to dialysis initiation was associated with greater survival during the first year following dialysis initiation [10]. To improve the recognition and facilitate management of patients with CKD, the National Kidney Foundation (NKF) developed the Kidney Disease Outcomes Quality Initiative (KDOQI).…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study of 556 patients initiating dialysis, receipt of quality care in the management of CKD-related complications prior to dialysis initiation was associated with greater survival during the first year following dialysis initiation [10]. To improve the recognition and facilitate management of patients with CKD, the National Kidney Foundation (NKF) developed the Kidney Disease Outcomes Quality Initiative (KDOQI).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the relationship between quality of pre-dialysis care and HRQoL at dialysis onset has not been investigated to date. However, numerous studies have shown associations between quality of pre-dialysis care and dialysis mortality on one hand [4] and, HRQoL at dialysis onset and dialysis mortality on the other hand [5-7]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a favourable association between early referral or a high number of pre-ESRD nephrology consultations and quality of therapeutic care has been suggested [11,12]. Likewise, quality of pre-ESRD therapeutic practices has been found to be associated with survival after RRT [4]. …”
Section: Introductionmentioning
confidence: 99%
“…This finding is in accordance with those of a prospective French study, which showed that the quality of CKD care was independently associated with better early survival on dialysis. 11 In addition, it matches with the positive impact of multidisciplinary care on some patients' early outcomes. 12 Early mortality in dialysis has multiple causes ( Figure 1).…”
mentioning
confidence: 68%